If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + 4) = 3x + 4 Combine like terms: 3 + 4 = 7 3(7) = 3x + 4 Multiply 3 * 7 21 = 3x + 4 Reorder the terms: 21 = 4 + 3x Solving 21 = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 21 + -3x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 21 + -3x = 4 + 0 21 + -3x = 4 Add '-21' to each side of the equation. 21 + -21 + -3x = 4 + -21 Combine like terms: 21 + -21 = 0 0 + -3x = 4 + -21 -3x = 4 + -21 Combine like terms: 4 + -21 = -17 -3x = -17 Divide each side by '-3'. x = 5.666666667 Simplifying x = 5.666666667
| 9x^2-26x-35=0 | | 10x=x+81 | | 3x-2(x-9)=2+2x | | 4x+2x-2=12 | | 9x-3+2x-5=2(4x-1) | | 4w-1+9w= | | 5x+17+7x-29=90 | | 5x+5=5y | | 120+-4.5=120 | | 2ax^2-4(a+1)x+4a+1=0 | | 4x^4-4x^3-17x^2-19x-6=0 | | 5x+4-8=18 | | 3n^2=-4n-1 | | 5(3k+2)=40 | | 6x-5+2x+43=90 | | 3+2(x+2)=15 | | 3(2y+1)=39 | | 2x+8=x+11 | | X=-0.5x+3 | | -7(2t+8)=-126 | | r+(-016)=0.37 | | 5(f-1)=-25 | | (7a^3-2a^2-4a+9)+(3a+6)-(-a^2-a+3)= | | 14x+18y=63 | | -9(T-2)-(t+3)=2 | | x+44=4x+17 | | 2(3x+4)=2x+1 | | 8(s-7)=-92 | | 3x-4=x-10 | | 3x+4+x+20=180 | | 8x+6y=120 | | S^2-s-12=0 |